Islamic finance: undergraduate education - Tahir, Sayyid (Islamic Research and Training Institute (IRTI), Islamic Development Bank, 2008)

(untitled)
Islamic finance literacy has become critical for the future growth of the Islamic financial sector in the twenty-first century. While a multi-pronged approach is called for, the focus in this paper is on the undergraduate programs in Islamic banking and finance. It analyses the state of teaching of Islamic banking and finance at the undergraduate level and proposes solutions for improving the undergraduate education of Islamic banking and finance.